2013
DOI: 10.1124/dmd.113.054239
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 mRNA Expression in the Rodent Brain: Species-, Sex-, and Region-Dependent Differences

Abstract: Cytochrome P450 (P450) enzymes play a critical role in the activation and detoxication of many neurotoxic chemicals. Although research has largely focused on P450-mediated metabolism in the liver, emerging evidence suggests that brain P450s influence neurotoxicity by modulating local metabolite levels. As a first step toward better understanding the relative role of brain P450s in determining neurotoxic outcome, we characterized mRNA expression of specific P450 isoforms in the rodent brain. Adult mice (male an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…The mechanistic basis for the sex difference in the extent of PB-induced hepatocyte proliferation and the apparent noninvolvement of CYP2B in the proliferative response in females are currently not understood, but they may be partly explained by the lower extent of hepatic CYP2B induction by PB in females than in males. In that regard, our present result was consistent with previous reports, that PB induced CYP2B10 to a larger extent in males than in females (Li-Masters and Morgan, 2001;Stamou et al, 2014) and that male mice were more susceptible to PB-induced hepatocarcinogenesis than female mice (Heindryckx et al, 2009;Maronpot, 2009). This sex difference in CYP2B inducibility by PB does not appear to be due to a difference in CAR expression, because cytosolic (Hernandez et al, 2009) or nuclear (Saito et al, 2013) CAR protein level was found to be similar between untreated male and female mice.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationsupporting
confidence: 83%
“…The mechanistic basis for the sex difference in the extent of PB-induced hepatocyte proliferation and the apparent noninvolvement of CYP2B in the proliferative response in females are currently not understood, but they may be partly explained by the lower extent of hepatic CYP2B induction by PB in females than in males. In that regard, our present result was consistent with previous reports, that PB induced CYP2B10 to a larger extent in males than in females (Li-Masters and Morgan, 2001;Stamou et al, 2014) and that male mice were more susceptible to PB-induced hepatocarcinogenesis than female mice (Heindryckx et al, 2009;Maronpot, 2009). This sex difference in CYP2B inducibility by PB does not appear to be due to a difference in CAR expression, because cytosolic (Hernandez et al, 2009) or nuclear (Saito et al, 2013) CAR protein level was found to be similar between untreated male and female mice.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationsupporting
confidence: 83%
“…3). In some brain regions, such as the cortex, hippocampus, striatum, and thalamus, PB and 2,4,6-tryphenyl dioxane did not affect CYP2B expression; in contrast, these agents caused a dramatic increase in CYP2B expression in the liver (Upadhya et al, 2002;Pustylnyak et al, 2009;Stamou et al, 2014). These results suggested that another mechanism, not involving CAR, may have contributed to the transcriptional activation of Ugt1a6 and Ugt1a7 in the rat brain.…”
Section: Discussionmentioning
confidence: 54%
“…A northern blot analysis demonstrated that CYP4X1 mRNA is strongly and specifically expressed in the rat brain stem, hippocampus, and vascular endothelial cells (Bylund et al, 2002). Stamou et al (2013) previously reported that CYP4X1 mRNA is equally detectable in the rat liver and brain. Al-Anizy et al (2006) showed the selective expression of Cyp4x1 in the mouse brain, while CYP4X1 mRNA was ubiquitously expressed in adult human tissues (Choudhary et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of brain and/or neural CYP enzymes and their localization as well as the identification of endogenous substrates and their metabolic endproducts will provide a better understanding of the role of CYP enzymes in brain physiology, development, and diseases (Ghosh et al, 2016;Toselli et al, 2016). It may also be qualitatively and quantitatively different from that in the liver due to differences in expression or to the presence of unique enzymes in the brain and particular neurons (Stamou et al, 2013). Furthermore, useful cell lines for drug metabolism studies in the brain have not yet been established.…”
Section: Introductionmentioning
confidence: 99%